Enhancing Multimodal Transportation Through Logistics Education: A Case Study Of Indonesian Institutes - Marihot Simanjuntak; Fahmi Umasangaji; Baihaqi Baihaqi; April Gunawan Malau; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This qualitative study examines the effectiveness of logistics education within Indonesian transportation institutes' multimodal transportation programmes. Fifty cadets were analysed, revealing a positive perception of logistics education's importance and its significant impact on student competency and operational efficiency. Themes emerged highlighting cadets' strong understanding and application of logistical principles, leading to tangible improvements in transportation costs, service quality, and work processes. The findings underscore the critical role of logistics education in preparing students for careers in the transportation sector and improving the efficiency and sustainability of transportation systems. Recommendations include curriculum enhancement, professional development for educators, industry engagement, and the integration of technology. By implementing these recommendations, educational institutions can better align their programmes with industry needs and ensure graduates are equipped to address the sector's challenges. This research contributes to the discourse on transportation education, emphasising the importance of logistics education in shaping the future of multimodal transportation in Indonesia and beyond.